The tensile and compressive properties of four experimental magnesium alloys assessed for light duty truck oil pans - Tanzer, Mehmet Barış. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Light weight design has a great importance in the development process of new automobiles. In recent years, the oil prices have increased and the exhaust gases of ignition engines have become a bigger concern for global warming. Many new materials, especially magnesium alloys, have been developed and introduced into the automobile industry to decrease the weight of the vehicles and to increase fuel efficiency. For these significant reasons, using the best material available to optimize the fuel economy is very important. In this thesis, four magnesium alloy compositions have been chosen, based on the AS21 and ACM522 magnesium alloys, suitable for light duty trucks oil pans. The experimental results of the microstructure, tensile strength, and compressive strength of the die cast alloys are presented for these compositions. In the metallographic analysis, Mg2Si and b-Mg17Al12 intermetallic phases have been observed. The intermetallic compound Mg2Si has appeared in two morphologies, polyhedral and the Chinese script. The b- Mg17Al12 intermetallic phase has been observed as blocky precipitates. The increase in the calcium content has been observed to increase the amount and thickness of the Mg2Si Chinese script phases present within the alloy. This has been observed to increase the strength of the alloys. In addition, a CAE analysis has been performed for modal analysis. The optimum composition for the light duty trucks oil pans is selected according to the results of these experiments.
Keywords: Magnesium alloys.